1997
DOI: 10.1164/ajrccm.155.3.9117014
|View full text |Cite
|
Sign up to set email alerts
|

Role of IgE in hyperresponsiveness induced by passive sensitization of human airways.

Abstract: Incubation of airways from nonatopic patients with serum from patients with high IgE levels confers responsiveness to "specific" (allergen) and hyperresponsiveness to "nonspecific" (histamine) stimuli. We have tested the hypothesis that the level of IgE determines the degree of specific and nonspecific responsiveness. Bronchial rings from nonatopic patients were sensitized overnight with serum containing high levels of allergen-specific IgE, or with an allergen-specific chimeric IgE (JW8) in physiologic buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 19 publications
10
61
1
1
Order By: Relevance
“…Considering all these data, it is possible to hypothesize an analogous pro-inflammatory and pro-constrictory activity of S-salbutamol also in equine airways after only 90 min. of incubation,enhancing the potency of histamine, as has been demosntrated in human bronchi after passive sensitization [26].…”
Section: Discussionmentioning
confidence: 88%
“…Considering all these data, it is possible to hypothesize an analogous pro-inflammatory and pro-constrictory activity of S-salbutamol also in equine airways after only 90 min. of incubation,enhancing the potency of histamine, as has been demosntrated in human bronchi after passive sensitization [26].…”
Section: Discussionmentioning
confidence: 88%
“…the incubation of isolated airways with IgE-rich serum obtained from atopic individuals, closely mimics features of bronchial hyperresponsiveness [22,33], a central abnormality in patients with asthma. It has been suggested that passive immune sensitization of human tissue confers an inherent change in the contractility of airway smooth muscle that may contribute to hyperresponsiveness, which could induce mast cell degranulation [33].…”
Section: Article In Pressmentioning
confidence: 78%
“…The sensitizing serum was prepared from the whole blood of patients suffering from atopic asthma (total IgE >250 u ml -1 , and specific IgE antibodies against common aeroallergens) during an exacerbation. Passive sensitization of human airway smooth muscle has been described previously [22]. Sera were not pooled but rozen at -80°C M A N U S C R I P T…”
Section: Tissue Preparationsmentioning
confidence: 99%
“…This concept is supported by several in vitro studies, which have shown that bronchial hyperresponsiveness in tracheal segments may occur after incubation with sera of patients with high IgE levels [33]. In this setting, it might be feasible to use monoclonal anti-IgE as asthma therapy even in nonallergic asthmatics.…”
Section: Discussionmentioning
confidence: 90%